Safety of Therapy with Tocilizumab and Other Interleukin Inhibitors - V. I. Petrov; A. Y. Ryazanova; D. A. Nekrasov; V. I. Svinukhov; N. S. Privaltseva (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
Monoclonal antibodies directed against interleukin and interleukin receptors have been successfully used for the treatment of rheumatic diseases since 2001, and since 2020 they have been used as part of complex therapy for patients with severe COVID-19. This raises the question of safety of these products, especially when used for new indications. The aim of the study was to analyse data on potential adverse reactions to tocilizumab and other interleukin inhibitors in order to increase the safety of pharmacotherapy of systemic connective tissue diseases, as well as of severe COVID-19. Literature data suggest that the most frequent adverse reactions to tocilizumab and other interleukin inhibitors are infections, hypercholesterolemia, leukopenia, neutropenia, thrombocytopenia, and increased liver enzyme activity. Hypersensitivity and acute infusion reactions, manifested as pseudoallergic reactions, also pose serious health risks and can even be fatal. However, the identification of undesirable reactions to interleukin inhibitors is challenging, due to their prolonged intake and long intervals between injections. Besides, they are often used in combination with other medicines, such as methotrexate or glucocorticosteroids, which complicates establishment of a reliable correlation between an adverse reaction and a particular medicine. At present, the safety of tocilizumab and other interleukin inhibitors for the treatment of severe COVID-19 has not been studied properly and needs further research with an increased number of participants and a careful analysis of the risk/benefit ratio of these medicines when used for COVID-19 treatment.